Role of serum sodium on heart, anemia, and diabetes patients - Mahashweta Das; Sunit Kumar Medda; Shipra Banik; Rabindra Nath Das (Academia Medicine)
This article examines the role of serum sodium (SNa) on heart, anemia, and diabetes patients based on a real data set of 299 patients and probabilistic modeling. It is derived herein that mean SNa is positively associated with the marginal effects of platelets count (PLC) (P = 0.0019), anemia status (ANS) (P = 0.1053) (partially), creatinine phosphokinase (CRP) (P = 0.0462), smoking habit (SMH) (P= 0.1017), SEX (P = 0.0029), and the joint interaction effects (JIEs) of ejection fraction (EJF) and the status of high blood pressure (HBP), i.e., EJF*HBP (P = 0.1398); ANS and death event (DEE), i.e., ANS*DEE (P = 0.0009); age and time to follow-up (TTF), i.e., AGE*TTF (P = 0.0700); age and serum creatinine (SEC), i.e., AGE*SEC (P = 0.0901); EJF and SEC, i.e., EJF*SEC (P = 0.0044); and CRP and TTF, i.e., CRP*TTF (P = 0.0021). Mean SNa is negatively associated with the marginal effects of DEE (P = 0.0001), TTF (P= 0.0521), SEC (P = 0.0028), diabetes status (DIS) (P = 0.0121), and the JIEs of PLC*ANS (P = 0.1064), CRP*SMH (P = 0.0274), CRP*HBP (P = 0.0044), AGE*PLC (P = 0.0811), AGE*SEX (P = 0.0008), AGE*CRP (P = 0.0463), and EJF*PLC (P = 0.0420). The variance of SNa is marginally positively associated with AGE (P = 0.0933), DEE (P = 0.1408), and the JIEs of AGE*ANS (P = 0.0575), EJF*SEX (P = 0.1001), SEC*SMH (P = 0.0091), EJF*TTF (P = 0.0008), CRP*DIS (P = 0.0039), EJF*DEE (P = 0.0022), and SEC*DIS (P = 0.0001). Also the variance of SNa is marginally negatively associated with ANS (P = 0.0631), EJF (P = 0.0008), DIS (P = 0.0548), PLC (P = 0.0023), SMH (P = 0.0242), TTF (P = 0.0018), CRP (P = 0.0027), and the JIEs of AGE*DEE (P = 0.0003) and SEC*SEX (P = 0.1327). SNa maintains a complex relationship with different patients and factors, and they have both marginal and JIEs on SNa. Medical practitioners and researchers should care about the complicated functional roles of SNa.